(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The complex Oxo 1,2-NNdimethyl hyrazido – bis (diethyl dithiocarbamato) molybdenum (a) Was prepared Via the intermediate complex di Oxo bis (diethyl dithiocarbamato) molybdenum (b) the two complex was characterized spectrophometrically by uv.vis. and FTIR technique . The kinetic of photolysis of complex (a) was studied that irradiate its solution by mono wavelength (366nm) which supplied from pressure medium mercury lamp (PMML) with of 4 watt at 20 Co for 90 min and ethanol as solvent . the reaction seems to first order of reaction and the first order constant was calculated by monitoring the spectroscppic change through irradiation process . several were studied include : complex concentration , light intensity , temperature , pH , solvent polarity and irradiation time . the result was found the photolysis rote of complex (a) propotional inversty wit concentration and it increase with light intensity increase temperature rise the photolysis rote and the activation energy was (23.971 , 12.742 kJ/mole) at 256 and 400 nm respectively . It that complex (a) degraded at pH =7 more than down and above pH =7.5 the complex (a) degraded in the changing of solvent according to the scquence isopropanol > 1- butanol > ethanol > methanol. The photolysis periol was found 390 for complete degradation .